Lead (Pb2+)-induced calcium oxalate crystallization ex vivo is ameliorated via inositol 1,4,5-trisphosphate receptor (InsP3R) knockdown in a Drosophila melanogaster model of nephrolithiasis. - Branco, A.J.; Vattamparambil, A.S.; Landry, G.M. (Environmental Toxicology and Pharmacology, 2021)
Nephrolithiasis causes severe pain and is a highly recurrent pathophysiological state. Calcium-containing stones, specifically calcium oxalate (CaOx), is the most common type accounting for approximately 75 % of stone composition. Genetic predisposition, gender, geographic region, diet, and low fluid intake all contribute to disease pathogenesis. However, exposure to environmental pollutants as a contribution to kidney stone formation remains insufficiently studied. Lead (Pb2+) is of particular interest as epidemiological data indicate that low-level exposure (BLL = 0.48-3.85 ?M) confers a 35 % increased risk of developing CaOx nephrolithiasis. However, mechanisms underlying this association have yet to be elucidated. Drosophila melanogaster provide a useful genetic model where major molecular pathophysiological pathways can be efficiently studied. Malpighian tubules (MT) were isolated from either Wild-Type or InsP3R knockdown flies and treated with oxalate (5 mM) ± Pb2+ (2?M) for 1 h. Following exposure, MTs were imaged and crystals quantified. CaOx crystal number and total area were significantly increased (5-fold) in Pb2+(pre-treatment) + oxalate-exposed MTs when compared to oxalate alone controls. However, CaOx crystal number and total crystal area in Pb2+ + oxalate-exposed InsP3R knockdown MTs were significantly decreased (3-fold) indicating the role for principal cell-specific InsP3R-mediated Ca2+ mobilization as a mechanism for Pb2+-induced increases in CaOx crystallization inset model of nephrolithiasis.